A Non-Radioactive DAPI-based High-Throughput In Vitro Assay to Assess Plasmodium falciparum Responsiveness to Antimalarials—Increased Sensitivity of P. falciparum to Chloroquine in Senegal - Ndiaye, Daouda (The American Society of Tropical Medicine and Hygiene, 2010)
The spread of Plasmodium falciparum drug resistance is outpacing new antimalarial development and compromising effective malaria treatment. Combination therapy is widely implemented to prolong the effectiveness of currently approved antimalarials. To maximize utility of available drugs, periodic monitoring of drug efficacy and gathering of accurate information regarding parasite-sensitivity changes are essential. We describe a high-throughput, non-radioactive, field-based assay to evaluate in vitro antimalarial drug sensitivity of P. falciparum isolates from 40 Senegalese patients. Compared with earlier years, we found a significant decrease in chloroquine in vitro and in genotypic resistances (> 50% and > 65%, respectively, in previous studies) with only 23% of isolates showing resistance. This is possibly caused by a withdrawal of chloroquine from Senegal in 2002. We also found a range of artemisinin responses. Prevalence of drug resistance is dynamic and varies by region. Therefore, the implementation of non-radioactive, robust, high-throughput antimalarial sensitivity assays is critical for defining region-specific prophylaxis and treatment guidelines.